A Reconfigurable Hardware Realization for Real-Time Simulation of Cardiac Excitation and Conduction - Mahmud, Farhanahani; Adon, Nur Atiqah; Othman, Norliza; Hakim, Ade Anggian; Morsin, Marlia; Jabbar, Mohamad Hairol (International Journal of Integrated Engineering, 2024)
Dynamic simulation of complex cardiac excitation and conduction requires high computational time. Thus, the hardware techniques that can run in real-time simulation were introduced. However, according to existing studies, the hardware simulation requires high power consumption and involves a large size of the physical parts. Due to the drawbacks, this research presents the adaptation of nonlinear Ordinary Differential Equation (ODE)-based cardiac excitable models of Luo-Rudy Phase I (LR-I) and FitzHugh-Nagumo (FHN) in a reconfigurable hardware of field-programmable gate array (FPGA). FPGA rapid prototyping using MATLAB Hardware Description Language (HDL) Coder was used to convert a fixed-point MATLAB Simulink blocks design of the cardiac models into a synthesizable VHSIC Hardware Description Language (VHDL) code and verified using the FPGA-In-the Loop (FIL) Co-simulator. The Xilinx FPGA Virtex-6 XC6VLX240T ML605 evaluation board was chosen as the FPGA platform. The cardiac excitation response characteristics using LR-I model and the simulations of reentrant initiation and annihilation using the FHN model were verifed in Virtex-6 FPGA. This means, a new real-time simulation-based analysis technique of cardiac electrical excitation and conduction were successfully developed using the reconfigurable hardware.